New terroirs: lessons from Hong Kong for seamless digital and physical interactions. (1st June 2022) - Kay-Jones, Simon; Janvier, Louise
Abstract : Many professions have struggled to translate their disciplines into a flexible blended learning experience that is adaptive to the recent pandemic constraints and responsive to the changing needs of learners, and which can match the vibrancy of a purely physical place of education. Architecture has been counter-intuitively resistant to a more seamless, adaptive and responsive environment as a digital learning space. This is due to an ambiguity of the tools and elements available to practitioners for positive learning environments that can be usefully transposed to blended learning. For an industry marked as creative, since the mid-2000s it has found itself behind that of service designs' educational development. Traditionalists in our discipline have continued to focus on the production and craft of artefacts in design over and above process. However, we have sought to balance this craft and process with the appropriate digital 'places' and 'positions' as an emerging 'place-free' praxis for education. We collectively refer to all of these as a 'terroir' for new places and alternative positions in education. In this article, we set out the ingredients and tools uncovered to deliver these progressive learning places within the new terroir, which are applicable to any creative industry. We also outline how to successfully promote agency within the learning process to foster creative education in a variety of design fields and assist in developing alternative school positions. The article explores the role that 'Process-to-strategy' has in facilitating creativity, while the 'Construct-a-journey' section describes the tools that are needed to enable students to fashion an autonomous learning path as a unified experience. Lastly, the 'Experience-the-terroir' section evaluates the inherent design possibilities in virtual environments across all themes and strategies to explore specific qualities of experience, which could lead to a greater understanding of the place containing design creativity, spatial illusion and design processes. The specific project that we discuss investigated the qualitative impacts of novel technologies adapted to the practice of architectural education along these four key themes. They are supportive to a peer-led, positive learning, transnational environment as a 'place-free' praxis, while providing a structured approach for reflexive educational design in a particular time of flux such as the recent pandemic. The article concludes with a summary of the new architectural terroir.